Penelitian Terbaru terhadap 3 (Tiga) Jenis Ekstrak Teripang di Pulau Tegal Mas, Lampung - Hutapea, Manuel; Swandiny, Greesty Finotory; Syafawi, M. Irfan; Putra, Fahreza Pratama; Kokadir, Sucipto; Basilianus, Edward; Putri, Vinessa Gracia; Abdillah, Syamsudin (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Sea cucumbers are deep-sea-dwelling invertebrate animals that are rich in nutrients and have been empirically used to prevent various degenerative diseases, especially due to their ability to dampen free radicals. The purpose of this study was to identify, and determine antioxidant activity, total phenolic content, and toxic properties in extracts of several sea cucumber species originating from Tegal Mas Island, Lampung. The identification results of the three sea cucumber species were Stichopus vastus Sluiter (SV), Stichopus monotuberculatus Quay & Gaimard (SM), and Stichopus quadrifasciatus Massin. (SQ). The extraction was performed by kinetic maceration against all parts of the sea cucumber using a 70% ethanol solvent. Antioxidant activity test using the DPPH (2,2-diphenylpicrilhydrazyl) free radical suppression method and determination of the total phenolic content using the Folin-Ciocalteu method. The results showed that SV had the highest total phenolics and antioxidants with the lowest toxicity. However, optimisation of extraction between wet and dry sea cucumbers is still required. Extraction optimisation with various solvents can also be done to gain secondary metabolites more effectively.